SARS-CoV-2 and Hypertension: Evidence Supporting Invasion into the Brain Via Baroreflex Circuitry and the Role of Imbalanced Renin-Angiotensin-Aldosterone-System - Oliveira, Kellysson Bruno; Melo, Igor Santana de; Silva, Bianca Rodrigues Melo da; Oliveira, Keylla Lavínia da Silva; Sabino-Silva, Robinson; Anhezini, Lucas; Katayama, Pedro Lourenco [UNESP]; Santos, Victor Rodrigues; Shetty, Ashok K; Castro, Olagide Wagner de (SAGE Publications, 2023)
Hypertension is considered one of the most critical risk factors for COVID-19. Evidence suggests that SARS-CoV-2 infection produces intense effects on the cardiovascular system by weakening the wall of large vessels via vasa-vasorum. In this commentary, we propose that SARS-CoV-2 invades carotid and aortic baroreceptors, leading to infection of the nucleus tractus solitari (NTS) and paraventricular hypothalamic nucleus (PVN), and such dysregulation of NTS and PVN following infection causes blood pressure alteration at the central level. We additionally explored the hypothesis that SARS-CoV-2 favors the internalization of membrane ACE2 receptors generating an imbalance of the renin-angiotensin-aldosterone system (RAAS), increasing the activity of angiotensin II (ANG-II), disintegrin, and metalloproteinase 17 domain (ADAM17/TACE), eventually modulating the integration of afferents reaching the NTS from baroreceptors and promoting increased blood pressure. These mechanisms are related to the increased sympathetic activity, which leads to transient or permanent hypertension associated with SARS-CoV-2 invasion, contributing to the high number of deaths by cardiovascular implications.
Keywords: angiotensin II; baroreflex; hypertension; SARS-CoV-2